2016
DOI: 10.1186/s13643-016-0376-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between surgeon volume and outcomes: a systematic review of systematic reviews

Abstract: BackgroundThe surgeon volume-outcome relationship has been discussed for many years and its existence or nonexistence is of importance for various reasons. A lot of empirical work has been published on it. We aimed to summarize systematic reviews in order to present current evidence.MethodsMedline, Embase, Cochrane database of systematic reviews (CDSR), and health technology assessment websites were searched up to October 2015 for systematic reviews on the surgeon volume-outcome relationship. Reviews were crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
175
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(195 citation statements)
references
References 70 publications
(201 reference statements)
7
175
3
3
Order By: Relevance
“…The SR/MA's quality seems to be low in many fields of medicine. Among studies published in medicine to September 2019, in which the AMSTAR 2 was used as an instrument to evaluate the quality of SR/MA, 23 of 31 papers produced results similar to our study . In the six studies, the methodological quality of most (around 60%) of SRs was critical low to low .…”
Section: Discussionsupporting
confidence: 70%
“…The SR/MA's quality seems to be low in many fields of medicine. Among studies published in medicine to September 2019, in which the AMSTAR 2 was used as an instrument to evaluate the quality of SR/MA, 23 of 31 papers produced results similar to our study . In the six studies, the methodological quality of most (around 60%) of SRs was critical low to low .…”
Section: Discussionsupporting
confidence: 70%
“…Previous investigators have demonstrated the volume-outcome association in many major surgeries. [10][11][12] In the field of urology, numerous studies focused on radical cystectomy and radical prostatectomy. 13,14 However, there is a paucity of data on the association between surgical volume and outcomes after nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…prostatectomy. [10][11][12][13][14] When it comes to the volume-outcome association in nephrectomy, studies in the literature almost exclusively focus on radical nephrectomy (RN) or partial nephrectomy (PN) for nonmetastatic RCC. 15 It is well documented that RN, PN, and CN have different surgical complexities and perioperative safety profiles.…”
mentioning
confidence: 99%
“…Dat bij het vaker uitvoeren van complexe behandelingen, zoals een robotgeassisteerde radicale prostatectomie (RARP), de ervaring van het chirurgische team groter wordt en daardoor de operatie-uitkomsten beter zullen zijn, is aannemelijk [4]. De leercurve voor de complexe (robot)operatie is immers lang en dat betekent dat je veel ingrepen moet doen om ten aanzien van uitkomsten een plateaufase te bereiken.…”
Section: Abstract Prostate Cancer Network · Regionalization · Value Bunclassified